Translating the Hebrew Name יהוה into the Yoruba language of Nigeria in the Yoruba Bible - David T. Adamo (In die Skriflig, 2019)
Scholars are not unanimous about the correct pronunciation of the tetragrammaton, YHWH. The exact origin and meaning of the name have also been a subject of debate among scholars. Since translation is also interpretation, no one can give a correct translation of any word without knowing the actual meaning. While the Septuagint (LXX) translates the Hebrew word יהוה into Kurios, an English translation (New Revised Standard Version – NRSV) translates it as LORD. The translation of יהוה into the Yoruba language in the Yoruba Bible is Oluwa which I consider unacceptable. The purpose of this article is to propose the translation of the Hebrew יהוה to the most appropriate Yoruba name for the supreme God (Olodumare instead of Oluwa) which cannot be misunderstood by any Yoruba reader.